Theory of Thermionic Carrier Injection in Graphene/Organic Schottky Interface - Ang, Yee Sin; Ang, L. K. (Frontiers in Materials, 2019)
Understanding the physics of charge transport in organic materials and charge injection across organic-based interface is critically important for the development of novel organic electronics and optoelectronics. Despite extensive efforts devoted to the study of transport and injection phenomena in organic materials and interfaces, the physics of thermionic carrier injection across graphene/organic interface remains largely incomplete thus far. Here we construct a model of thermionic carrier injection across a graphene/organic Schottky interface based on the Lengevin theory of charge recombination and the detailed balance formalism. We show that, due to the strong electrostatic doping effect in graphene under the influence of an external gate voltage, the electrical current traversing the interface differs significantly from conventional bulk-metal/organic Schottky interface and the injection current can be efficiently modulated by a gate-voltage to achieve an on-off ratio well-exceed $10^7$. The model developed here shall provide a theoretical foundation for the understanding graphene/organic Schottky interface, thus paving the way towards the development of novel nanoscale graphene-hybrid organic electronic and optoelectronic devices.